Measuring the relative competitiveness of global deciduous fruit supply chains : South Africa versus Chile - Mashabela, Tebogo Edwin (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScAgric)--University of Stellenbosch, 2007.